An epidermal keratinocyte homogenate induced type 2 and proinflammatory cytokine expression in cultured dermal cells. Issue 2 (May 2022) - Murakami, Shokei; Futamura, Kyoko; Matsumoto, Kenji; Adachi, Yuichi; Matsuda, Akio
Abstract: Background: The "itch-scratch cycle" is a clinically well-known cause of exacerbation of atopic dermatitis (AD), but the underlying molecular mechanisms remain largely unknown. Objective: To test our hypothesis that some molecules released from damaged epidermal keratinocytes by scratching inducetype 2 responses in intact skin dermal cells, leading to exacerbation of AD. Methods: Normal human dermal fibroblasts (NHDF) and human dermal blood microvascular endothelial cells (HMVEC-dBl) were treated with an epidermal keratinocyte homogenate (EKH). We used qPCR and ELISA, respectively, to measure the mRNA expressions and protein concentrations of various cytokines, including IL-6, IL-8, thymic stromal lymphopoietin (TSLP), and IL-33. We analyzed IL-33 protein expression in the nuclear fractions of NHDF by Western blotting. We also investigated the effects of IL-1R1 gene-silencing and several AD therapeutic drugs on EKH induction of cytokine production by the dermal cells. Results: EKH significantly induced IL-6 and IL-8 in NHDF and HMVEC-dBl. EKH also induced type 2 cytokines, TSLP and IL-33, in NHDF. IL-1R1 gene-silencing in NHDF partially attenuated the induction. Dexamethasone (a corticosteroid) significantly inhibited, while ABT494 (a JAK1 inhibitor) partially inhibited, EKH's induction of cytokines in fibroblasts. In contrast, ABT494 was more effective than dexamethasone in inhibiting the cytokine induction in HMVEC-dBl. Conclusion: This study showed that a homogenate of epidermal keratinocytes significantly induced AD-related cytokines in cultured dermal cells, and IL-1α, an alarmin, might be involved in that induction. Combined use of corticosteroids and JAK1 inhibitors is likely to block the itch-scratch cycle by targeting different types of dermal cells. Highlights: The "itch-scratch cycle" is a clinically well-known cause of exacerbation of atopic dermatitis (AD). A homogenate of epidermal keratinocytes significantly induced AD-related cytokines in dermal cells. IL-1α, an alarmin, might be partially involved in that induction. Corticosteroids are effective in suppressing fibroblasts' inflammation due to disruption of keratinocytes by scratching. In contrast, JAK1 inhibitors may effectively suppress vascular endothelial cells' role in dermal inflammation.